Correlation of the Overactive Bladder Symptom Score, and the Voiding Diary and Urodynamic Parameters in Patients with Overactive Bladder Syndrome. Issue 3 (9th October 2013) - SONG, Miho; CHUN, Ji‐Youn; YOO, Dae Sun; HAN, Ji‐Yeon; CHOO, Myung‐Soo
<x xml:space="preserve">Abstract</x> Objectives To investigate correlations between the overactive bladder symptom score (OABSS), the voiding diary, and urodynamic parameters in women with overactive bladder syndrome (OAB). Methods A data analysis was performed on 164 women who presented with OAB between January 2006 and December 2011. All patients completed a 3‐day voiding diary, OABSS (frequency [Q‐F], nocturia [Q‐N], urgency [Q‐U], urgency incontinence [Q‐UI]), and a urodynamic study. The relationships of the OABSS, voiding diary variables, and urodynamic parameters, such as detrusor overactivity (DO) and maximal cystometric capacity (MCC), were analyzed. We used univariate and multivariate regression analysis to compare the bladder diary and OABSS. Detrusor overactivity and other variables were compared using logistic regression analysis. Results The 24‐h frequency, voided volume, and presence of urgency in the voiding diary were 9.8 ± 3.2 events/day, 176.6 ± 5.8 mL, and 70.7%. The 24‐h frequency and the voided volume recorded were significantly associated with Q‐F (P < 0.001, P < 0.001) and Q‐N (P = 0.008, P = 0.005). The presence of urgency recorded was associated with Q‐U in multivariate analysis (P = 0.012). The predictive factors related to DO was Q‐U in multivariate analysis. The MCC was found to correlate with the voided volume, urgency episode, Q‐F. Conclusions The OABSS correlate well with the voiding diary and urodynamic parameters and could be a useful tool to diagnose OAB when there is an absence of voiding diary and to later monitor OAB symptoms and treatment interventions.